Assessing a novel smartphone application - SnapCard, compared to five imaging systems to quantify droplet deposition on artificial collectors - Ferguson, J. Connor; Chechetto, Rodolfo G. [UNESP]; O'Donnell, Chris C.; Fritz, Brad K.; Hoffmann, W. Clint; Coleman, Chet E.; Chauhan, Bhagirath S.; Adkins, Steve W.; Kruger, Greg R.; Hewitt, Andrew J. (Elsevier B.V., 2016)
Previous work sought to compare the results from imaging software for characterising droplet coverage, but none exists examining these five software programs: Droplet Scan (R), Swath Kit (R), Deposit Scan, Image J, and Drop Vision (R)-Ag. Additionally, a freely available smartphone application (App), SnapCard was developed to provide an extension tool for in-field analysis of spray collectors, but nothing has been published regarding its comparison to other imaging software systems. The present study was conducted to compare five existing imaging software types against the new App, SnapCard. Six nozzles producing different spray qualities were selected to spray a water + Brilliant Blue Dye solution over two artificial collector types (water sensitive paper and Kromekote (R)). Each collector was assessed for percent coverage using the five imaging systems and SnapCard. Objectives of this study were: 1. To establish a baseline dataset using the sprayed cards and five commonly used imaging systems, and compare the coverage results from each. 2. Use the baseline data from Objective 1 as a measurement of precision to judge the results from SnapCard. 3. Make an assessment of SnapCard against the other imaging software type data in the study. Results showed that SnapCard has similar measured coverage means compared to other image analysis systems. For both collector types, SnapCard measured coverage within one standard deviation of the means across nozzle types. SnapCard is able to provide an immediate answer without expensive software or needing a laboratory to measure sprayed collector coverage with precise results, which further underscores its value. The other software types were not all similar for coverage, but the data followed the same trends for droplet size. Increasing the droplet size consistently decreased the coverage, across both collector types. Droplet Scan reported the highest coverage while Drop Vision-Ag and Swath Kit gave lower coverage values on water sensitive paper and Kromekote (R) collectors, respectively. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Image analysis; Kromekote; Water-sensitive paper; SnapCard; Smartphone App; Sprays; Droplet size; Spray quality